Wages, collective bargaining and recovery from the crisis in the Netherlands - Maarten van Klaveren; Kea Tijdens (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2015)
After the Second World War in the Netherlands, one of the most open economies in the world, wage moderation has be a leading theme in macroeconomic policy and industrial rela-tions. When wage restraint met with an overheated labour market and strike movements, social partners accepted the re-placement of a voluntary "social minimum wage" by a statutory minimum wage, introduced in 1969. Due to governmental freezes in the 1990s and 2000s the statutory minimum wage fell relative to the average wage, which left room for the in-crease of low-wage employment. In the 2000s the Dutch econ-omy generated large trade surpluses. However, in 2008-13 domestic private consumption fell substantially and this has, in combination with a housing bubble, seriously frustrated the recovery of the Dutch economy from the crisis. Continuing the Dutch wage moderation tradition in current conditions would cause negative effects, not only on domestic demand but also on the countrys labour productivity and growth potential. Thus, there are good reasons to defend a wage-led strategy as a recovery option in the case of the Netherlands.
Keywords: 330